Terapi Komplementer Menggunakan Aromaterapi Minyak Esensial Berpengaruh Terhadap Insomnia Pada Ibu Menopause di ATMA Home Care Poncokusumo - rufaindah, Ervin; Patemah, Patemah (Universitas Tribhuwana Tunggadewi, 2022)
Women will experience menopause physiologically at the age of 45 and show different signs symptoms. Menopause can cause psychological disturbances like frequent drowsiness, difficulty concentrating, insomnia, and fatigue. This study aimed to determine the effect of essential oil aromatherapy on insomnia. The pre-experimental design was used, with the One Group Pretest-Posttest approach to 30 menopausal women with insomnia in the ATMA Home Care Poncokusumo area, Malang Regency. The sampling technique chosen was accidental sampling. The data on insomnia was examined by modifying the KSPBJ-IRS-10 questions. The differences between groups were analyzed using the Wilcoxon Signed Rank Test. The respondents' age ranged between 46-53 years old (average 48 years), the average length of menopause was two years, and most graduated from high school, with mild insomnia. After the treatment, the respondents experienced a decrease in insomnia with a smaller mean score (19.5 to 11.5), p-value = 0.000 0.05, which means that there was a significant difference between the score of insomnia. It can be concluded that aromatherapy of essential oils can reduce the degree of insomnia in menopausal women. It is recommended to properly monitor the evaluation of the use of aromatherapy online and through home visits, as well as measure the characteristics of respondents.